DEVELOPMENT RESEARCH OF THE ENGLISH VOCABULARY OF CLASH OF CLANS GAME PLAYERS: ADULT PLAYERS - Sepnanda, Nina (Jurnal Gramatika, 2018)
ABSTRACTEnglish language is a global language. In order to face the globalization, people have to learn the English language. There are so many ways to develop English vocabulary such as reading bilingual dictionaries, listening to music, speaking to English natives speakers, or even playing games. There some research about learning English by playing games. This research tries to analyze the development of the English vocabulary of the video game players and measure the development either. In this research, the writer made adult players as the target. The writer uses a qualitative method to do this research. Living in the world of technology, the writer decides to use an online questionnaire. Based on the data, there are some characteristics of the video game that develop English vocabulary of the adult players'. The percentage of the English vocabulary development of Clash of Clans game players that is adult players’ is 55%.